Can Your DNA Influence Your Bet-Placing? The Impact of Cannabinoid Receptor 1 Gene on Gambling Tasks - Qin, Huihui; Zeng, Jianmin; Chen, Hong; Deng, Ling; Su, Li (Frontiers in Human Neuroscience, 2018)
Are we placing a bet by ourselves or has our DNA already made the decision for us? Previous research has suggested that some genes can influence our decision-making, but little is known about whether Cannabinoid Receptor 1 Gene (CNR1) can impact on how much people bet. To investigate this issue, we focused on rs1049353, a single nucleotide polymorphism of CNR1, because it is related to addictive behavior and reward processing. In this study (N = 377), we used a modified Cambridge gambling task (MCGT) to test the effect of rs1049353 polymorphism within CNR1 on how much people bet in gambling. We found that participants who are homozygous for C allele placed significantly larger bets than C/T carriers [F(1, 371) = 7.805, P = 0.005]. We further studied gene expression map in human and found that the CNR1 gene is overexpressed in striatum, amygdala and hippocampus. These brain structures are known to underpin reward and risk processing. Our findings suggest that, to some extent, high-level social decision-making like bet-placing could be influenced by a single genetic locus variation in healthy volunteers. In addition, such effects were likely to be mediated by key brain regions in the reward and risk processing networks.